Technical-tactical differences between female and male elite football: A data mining approach through neural network analysis, binary logistic regression, and decision tree techniques - Iván-Baragaño, I.; Maneiro, R.; Losada, J. L.; Casal, C. A.; Ardá, A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
The technical*tactical performance of women`s football has improved markedly in recent years. Despite this improvement, there are still differences between men`s football and women`s football. The objectives of this study were to know the technical and tactical key performance indicators (KPIs) that differentiate elite men`s and women`s football teams as well as to determine which statistical techniques demonstrate superior classification ability and interpretability in football terms. For this purpose, 768 matches corresponding to the latest editions of the UEFA Champions League, UEFA Euro and FIFA World Cup for men and women were analyzed. First, the differences at the bivariate level were analyzed using student`s t -test for independent sample ( p < 0.05) for the male and female teams. Secondly, three data mining classification algorithms were applied: (i) Artificial Neural Network (ANN), (ii) Binary Logistic Regression, and (iii) Decision Tree. Significant differences were found between men`s football and women`s football in variables related to technical elements such as lost balls (ES = 1.19), ball recoveries (ES = 1.00), and accurate passes (ES = 0.97), as well as regulatory aspects like fouls (ES = 0.59), successful tackles (ES = 0.46), and yellow cards (0.45). On the other hand, the classification models presented excellent or good predictive capability [Range AUC 0.774*0.982], with very small differences between the ANN`s and logistic regression models. This result justifies the use of simpler models as the linear regression model to understand the differences between men`s and women`s football. Moreover, the observed differences may offer insights for future efforts aimed at enhancing the performance of women`s football.